Effectiveness of load-level isolation system for pallet racking systems - Donà, Marco; Bernardi, Enrico; Zonta, Alberto; Ceresara, Marco; da Porto, Francesca (Frontiers in Built Environment, 2022)
Recent Italian earthquakes have shown the high seismic vulnerability of pallet racking systems. In the down-aisle direction and in the absence of bracing systems, these structures are very flexible moment-resisting frames. Instead, in the cross-aisle direction they consist of slender trusses, stiffened by various bracing systems; the latter, although necessary for lateral stability, attract significant seismic accelerations, which can cause the stored goods to fall, posing a threat to human safety. To reduce this risk while increasing the rack structural performance, some mitigation systems were proposed, based on specific base-isolation or dissipation devices. In this paper, an innovative passive control system is investigated, i.e., the Load-Level Isolation System (LLIS), which consists of applying isolators to the load level to control the movement of pallets in the cross-aisle direction. The LLIS is based on the Tuned Mass Damper (TMD) strategy and exploits the high payload of these structures. Among the major uncertainties of this system are the amount of isolated mass and its position within the structure. Therefore, for a case study rack, the LLIS parameters (isolation stiffness and damping ratio) are optimized for various arrangements of this system, considering cases with one or two isolated levels. The applied optimization procedure is an extension of the classical TMD approaches. The effectiveness of the optimized LLISs is then investigated through bidirectional Time-History analyses on 3D Finite Element rack models. The results show that using the LLIS, even on a single load-level, can greatly reduce the upright stresses and the cross-aisle displacements and accelerations, and that the optimal position of the LLIS is in the upper part of the rack.